2011
DOI: 10.1242/jeb.051565
|View full text |Cite
|
Sign up to set email alerts
|

Social interactions influence dopamine and octopamine homeostasis in the brain of the ant Formica japonica

Abstract: SUMMARYIn ants, including Formica japonica, trophallaxis and grooming are typical social behaviors shared among nestmates. After depriving ants of either food or nestmates and then providing them with either food or nestmates, a behavioral change in type and frequency of social interactions was observed. We hypothesized that starvation and isolation affected levels of brain biogenic amines including dopamine (DA) and octopamine (OA) -neuromediators modifying various insect behaviors -and tested the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…On the other hand, our data demonstrated that, in the queens, even if OA level in the brain is kept high; aggressive motivation seems to be kept low to evoke just threat behavior, if activity of N-acetylation in the brain is enhanced. Our studies also suggest that the 5-HTergic and DAergic systems are not closely linked to motivating aggressive behavior, although the 5-HTergic system might be linked to an evoked aggression as shown by Kostowski et al [6], and DAergic system in the brain, on the other hand, is demonstrated to be linked to social interaction in the ant [5]. We also observed that social interaction maintains contents of biogenic amine in the brain.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…On the other hand, our data demonstrated that, in the queens, even if OA level in the brain is kept high; aggressive motivation seems to be kept low to evoke just threat behavior, if activity of N-acetylation in the brain is enhanced. Our studies also suggest that the 5-HTergic and DAergic systems are not closely linked to motivating aggressive behavior, although the 5-HTergic system might be linked to an evoked aggression as shown by Kostowski et al [6], and DAergic system in the brain, on the other hand, is demonstrated to be linked to social interaction in the ant [5]. We also observed that social interaction maintains contents of biogenic amine in the brain.…”
Section: Discussionsupporting
confidence: 70%
“…Biogenic amines in the ant brain were measured using high-performance liquid chromatography (HPLC) with electrochemical detection (ECD). The detail of the HPLC-ECD system was described in our previous report [5]. In short, an ant was quickly frozen using liquid N 2 and the brain was dissected out in ice cold saline.…”
Section: Introductionmentioning
confidence: 99%
“…japonica [Wada-Katsumata et al, 2011] a ; P. dentata C. mus [Falibene et al, 2012] a ; P. dentata Predatory aggression F. japonica [Aonuma and Watanabe, 2012b] Production of oocytes and haploid egg laying, but not dealation, can be decreased by treatment with a tyrosine hydroxylase inhibitor, which leads to lowered DA titers. In honeybees, queen mandibular pheromone reduces DA levels of young workers inside the nest; decreased DA reduces locomotion, which may increase worker brood care [Beggs et al, 2007].…”
Section: Reproductive Dominance and Colony Foundationmentioning
confidence: 99%
“…In uncoordinated transportation, ants 15 pull a food item in opposite directions [8], resulting in slow-speed transportation 16 and/or frequently reaching a deadlock. In encircling coordinated transportation, ants 17 encircle a food item and the majority of members align at the side of the moving front 18 and pull it, whereas minor members align at the back and pull, lift, or push it. This 19 behavior achieves quick transportation, rarely reaching a deadlock.…”
mentioning
confidence: 99%
“…The ants, F. japonica are widely distributed in Japan [13,14] and have been 43 investigated particularly with regard to landmark navigation [15], social 44 interaction [16,17], etc. Most ants of this species lives under open ground and 45 …”
mentioning
confidence: 99%